Can adaptive clinical trials help to solve the productivity crisis of the pharmaceutical industry? A scenario analysis - Jörg C. Mahlich; Arne Bartol; Srirangan Dheban (Health Economics Review, 2021)
Aim: The productivity of pharmaceutical research and development (R&D) investments is declining due to high failure rates in clinical research. Recently, the US Food and Drug Administration (FDA) acknowledged that adaptive designs can make drug development more efficient and less costly. Our objective is to simulate cost-saving effects and estimate the impact on global R&D expenditures as well as possible outcomes measured in life-years gained. Methods: Based on published drug-development cost data we calculate potential cost savings derived from variations in clinical success rates that result from employing adaptive trial designs. In a subsequent step we estimate how those cost changes affect global R&D expenditures and outcomes. Results: Our calculations indicate that an adaptive trial design with the potential to increase success rates of clinical trials by 4 percentage points could lower development costs for a new drug from 2.6 to 2.2bn USD. On a global scale, this cost reduction would free up an additional 4.2bn USD for investment into pharmaceutical R&D to bring about drug innovations that in turn would be capable of generating up to 3.5 million life-years. Conclusion: New clinical trial designs are crucial to improving productivity within the pharmaceutical industry and to fostering a sustainable health-care system.
Keywords: 330